Healthcare providers’ palliative care graded diagnosis and treatment behavior, attitudes, self-efficacy, compassion fatigue, and workplace well-being: A mediating moderation model - Lixiang Liu; Meidi Xiong; Fang Hong; Yiting Zhang; Chunhua Zhang (PLoS ONE, 2025)
Background Palliative care is essential for end-of-life (EOL) patient care. While prior research has acknowledged the role of self-efficacy in nursing, its specific mechanisms within graded diagnosis and treatment contexts remain underexplored. Aims (1) To investigate the relationship between healthcare providers’ attitudes and behaviors regarding palliative care, graded diagnosis, treatment and the mediating role of self-efficacy. (2) To explore whether self-efficacy moderates the effect of compassion fatigue on well-being at work. Design A cross-sectional study was conducted at two tertiary hospitals in Hubei Province, China, and data were collected from 900 healthcare providers in July and August 2023. Methods Four validated self-report scales (Palliative Care Graded Diagnosis and Treatment Knowledge, Attitude, and Behavior scale, Self-Efficacy Scale, Brief Compassion Fatigue Scale, and Nurses’ Well-being at Work Scale) were used to collect data. Analyses were performed using SPSS PROCESS. Results Significant correlations were found among healthcare providers’ attitudes toward graded diagnosis and treatment, self-efficacy, and their behaviors. Healthcare providers’ attitudes towards graded diagnosis and treatment predicted an increase in self-efficacy (β = 0.161, p < 0.001), which subsequently led to improved graded diagnosis and treatment behavior (β = 0.647, p < 0.001). Self-efficacy mediated 34.81% of the effect of attitudes on graded diagnosis and treatment behavior. Although significant correlations existed among healthcare providers’ compassion fatigue, self-efficacy, and well-being at work, further analysis revealed that self-efficacy played a moderating role. Conclusion Self-efficacy plays a crucial role in palliative care graded diagnosis and treatment, moderating the relationship between compassion fatigue and well-being at work. This finding indicates that enhancing self-efficacy not only improves nursing practice in palliative care but also alleviates emotional stress and boosts professional well-being.